The frequency of CD38+ alveolar macrophages correlates with early control of M. tuberculosis in the murine lung - Pisu, Davide; Johnston, Luana; Mattila, Joshua T.; Russell, David G. (Nature communications, 2024)
Tuberculosis, caused by Mycobacterium tuberculosis , remains an enduring global health challenge due to the limited efficacy of existing treatments. Although much research has focused on immune failure, the role of host macrophage biology in controlling the disease remains underappreciated. Here we show, through multi-modal single-cell RNA sequencing in a murine model, that different alveolar macrophage subsets play distinct roles in either advancing or controlling the disease. Initially, alveolar macrophages that are negative for the CD38 marker are the main infected population. As the infection progresses, CD38 + monocyte-derived and tissue-resident alveolar macrophages emerge as significant controllers of bacterial growth. These macrophages display a unique chromatin organization pre-infection, indicative of epigenetic priming for pro-inflammatory responses. Moreover, intranasal BCG immunization increases the numbers of CD38 + macrophages, enhancing their capability to restrict Mycobacterium tuberculosis growth. Our findings highlight the dynamic roles of alveolar macrophages in tuberculosis and open pathways for improved vaccines and therapies. Mycobacterium tuberculosis infection remains a global health crisis. Here researchers characterise the alveolar macrophage subsets in a murine model of BCG vaccination in mice and link increases of CD38+ macrophages with restriction of bacterial growth.